A 2D/1D TiO2 nanosheet/CdS nanorods heterostructure with enhanced photocatalytic water splitting performance for H2 evolution. (12th April 2018) - Wang, Junmei; Wang, Zhijian; Qu, Peng; Xu, Qinchao; Zheng, Jianfeng; Jia, Suping; Chen, Jiazang; Zhu, Zhenping
Abstract: TiO2 with exposed (001) facets were composited with CdS nanorods to construct 2D/1D heterojunction. As comparison, P25 with mainly exposed (101) facets were employed to combine with CdS nanorods. The 2D/1D heterojunction of TiO2 nanosheets and CdS nanorod displayed 3.7 times higher hydrogen generation than that of P25/CdS composites. The results indicated that TiO2 with exposed (001) facets were favorable for enhancing the photocatalytic activity of CdS via optimizing the heterojunction between TiO2 and CdS. Photoluminescence and photoelectrochemical characteristics results demonstrated that the 2D-TiO2 /1D-CdS heterojunction exhibits higher separation efficiency of photoinduced carriers and superior electron transfer ability. This work exemplifies that heterojunction modification is an effective strategy to improve the efficiency of the photocatalyst composites. Highlights: Strong coupling effect contributed to excellent photocatalytic activity of TiO2 /CdS. The exposed (001) facet of TiO2 optimized the interface of TiO2 /CdS heterostructure. The photoinduced electrons transfer fluently via the built interface electric field.